2017
DOI: 10.1038/s41598-017-18278-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on incidence and prognosis of acute myeloid leukemia and acute promyelocytic leukemia: A meta-analysis

Abstract: Previous studies have demonstrated an association between high body mass index (BMI) and acute myeloid leukemias (AML), particularly acute promyelocytic leukemia (APL). However, the effect of obesity and overweight on the incidence of AML is not supported by all studies, and the relationship between obesity and prognosis of AML and APL has not been established. Thus, we conducted a meta-analysis to determine the role of BMI on the risk and clinical outcome of AML, including APL. Twenty-six eligible studies enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 53 publications
2
36
0
4
Order By: Relevance
“…Regarding the clinical outcomes, we found that, in line with the previous study by Breccia et al, Li et al, and Castillo et al, overweight/obese APL patients had lower OS . However, we were not able to reproduce the higher relapse risk reported in the Italian study of adult APL patients homogeneously treated with ATRA and chemotherapy (5‐year CIR 32% in APL with BMI ≥25% vs 11%).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Regarding the clinical outcomes, we found that, in line with the previous study by Breccia et al, Li et al, and Castillo et al, overweight/obese APL patients had lower OS . However, we were not able to reproduce the higher relapse risk reported in the Italian study of adult APL patients homogeneously treated with ATRA and chemotherapy (5‐year CIR 32% in APL with BMI ≥25% vs 11%).…”
Section: Discussionsupporting
confidence: 45%
“…To our knowledge, this is the largest study analysing the prognostic impact of overweight/obesity, as we studied 1320 APL patients, as compared with previous studies, Castillo et al (n = 446), Breccia et al (n = 144), Estey et al (n = 120 patients), and by Jeddi et al (n = 39). In addition, Li et al, performed a metanalysis including 866 APL patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The geographic variation suggests a possible genetic predisposition or environmental exposures to specific risk factors. Other factors such as obesity and dietary patterns have been linked to APL [36,37]. An increased BMI has been independently associated with a higher incidence of APL in Latino patients living in the USA [37].…”
Section: Acute Myelogenous Leukemiamentioning
confidence: 99%